Hallazgos bioquímicos y ecográficos en caninos obesos - Soto Alvarado, Christiane (2024)
The aim of this study was to identify comorbidities in obese canines attending Centro de Veterinaria y Zootecnia CES, Medellín, Colombia. Thirty canines with a body condition of 7/9 to 9/9 were evaluated. Those with signs of systemic disease or endocrinopathy were excluded. An evaluation of body condition, abdominal ultrasound (with emphasis on pancreas, liver and adrenal glands), non-invasive blood pressure measurement and blood analysis of cholesterol, triglycerides, glucose and canine-specific pancreatic lipase (cPLI) were performed. The results showed that 19 individuals presented hypertriglyceridemia, and those with higher triglyceride values presented ultrasound findings of vacuolar liver disease (p<0.01). Systolic blood pressure, cholesterol, glucose and cPLI were found within normal ranges and without differences between body condition ranges. The importance of including abdominal ultrasound in the diagnosis of obese patients is highlighted. It is concluded that hypertriglyceridemia associated with obesity leads to the accumulation of hepatic fatty infiltrates and vacuolar liver disease.